PENGARUH COVID-19 TERHADAP IHSG DENGAN NILAI TUKAR RUPIAH SEBAGAI VARIABEL MEDIASI - Agung Hendra Kusuma; Taufiq Andre Setiyono (LPPM POLITEKNIK LP3I BANDUNG, 2021)
This research aimed to examine the effect of the covid 19 against IHSG by the rupiah as mediation. This research was conducted using secondary data. The population and samples in this research were all confirmed positive cases of Covid-19 in Indonesia and the IHSG data and the rupiah exchange rate for the period March to December 2020. This research uses Sobel test with PLS tool. The conclusion of the research states that the covid-19 has a significant negative effect on the rupiah exchange rate, the covid-19 directly has a significant negative effect on the IHSG, the rupiah exchange rate has a significant positive effect on the IHSG, and the rupiah exchange rate does not mediate the effect of the covid-19 against the IHSG. Key words: covid-19, IHSG, Exchange rate